Natural pentacyclic triterpenoid from Pristimerin sensitizes p53-deficient tumor to PARP inhibitor by ubiquitination of Chk1 - Li Tao; Xiangyu Xia; Shujing Kong; Tingye Wang; Fangtian Fan; Weimin Wang (Elsevier, 2024)
Inhibition of checkpoint kinase 1 (Chk1) has shown to overcome resistance to poly (ADP-ribose) polymerase (PARP) inhibitors and expand the clinical utility of PARP inhibitors in a broad range of human cancers. Pristimerin, a naturally occurring pentacyclic triterpenoid, has been the focus of intensive studies for its anticancer potential. However, it is not yet known whether low dose of pristimerin can be combined with PARP inhibitors by targeting Chk1 signaling pathway. In this study, we investigated the efficacy, safety and molecular mechanisms of the synergistic effect produced by the combination olaparib and pristimerin in TP53-deficient and BRCA-proficient cell models. As a result, an increased expression of Chk1 was correlated with TP53 mutation, and pristimerin preferentially sensitized p53-defective cells to olaparib. The combination of olaparib and pristimerin resulted in a more pronounced abrogation of DNA synthesis and induction of DNA double-strand breaks (DSBs). Moreover, pristimerin disrupted the constitutional levels of Chk1 and DSB repair activities. Mechanistically, pristimerin promoted K48-linked polyubiquitination and proteasomal degradation of Chk1 while not affecting its kinase domain and activity. Importantly, combinatorial therapy led to a higher rate of tumor growth inhibition without apparent hematological toxicities. In addition, pristimerin suppressed olaparib-induced upregulation of Chk1 and enhanced olaparib-induced DSB marker γΗ2ΑΧ in vivo. Taken together, inhibition of Chk1 by pristimerin has been observed to induce DNA repair deficiency, which may expand the application of olaparib in BRCA-proficient cancers harboring TP53 mutations. Thus, pristimerin can be combined for PARP inhibitor-based therapy.